Characterization of ZnO and Fe doped ZnO nanoparticles using fluorescence spectroscopy - Singhal, Rahul; Fernando, Mihiri; LeMaire, Peter K.; Wu, Binlin (Oxide-based Materials and Devices X, 2019)
In this study, nanoparticles of pure zinc oxide (ZnO) and ZnO doped with iron of various doping concentrations (Zn1- xFexO) are analyzed using fluorescence spectroscopy. Excitation and emission spectra using various operating wavelengths were collected. Individual spectra and excitation emission matrix were analyzed. Various peaks including strong ultraviolet (UV) emission peaks and strong blue emission peaks that are corresponding to the near-band-edge emission (NBE) and defect emission (DE) peaks were studied based on the peak intensities, peak wavelengths, and NBE peak to defect peak ratios. The Zn1-xFexO materials were also analyzed using X-ray diffraction and optical absorption spectroscopy. The variation in the band gap energy and in the NBE emission energy with dopant concentration was analyzed. A red-shift was observed with the NBE emission peak. The NBE to DE ratio initially increases from pure ZnO to Zn0.97Fe0.03O and then decreases as the dopant concentration increases.
Keywords: Absorption spectroscopy; Band Gap; Band-edge emission (NBE); Band-edge emissions; Defect emission; Defect emission (DE); Defects; Dopant concentrations; Doping concentration; Emission spectroscopy; Energy gap; Excitation and emission spectra; Excitation emission matrices; Fluorescence; Fluorescence spectroscopy; II-VI semiconductors; Iron; Laser radiation; Light absorption; Nanoparticles; Near band edge emissions; Red Shift; Semiconductor doping; X ray diffraction; X-ray diffraction; Zinc oxide; Zinc oxide (ZnO); ZnO nanoparticles; dept.phy

Effect of binder concentration on ternary MnO2/CuS/reduced graphene oxide material for supercapacitor applications - Chaudhary, Manika; Oyelola, Lekan; Glidden, Thomas; Broadbridge, C.; LeMaire, Peter; Sharma, Rakesh; Singh, Vinamrita; Sahi, Vikhyat; Singhal, Rahúl (Journal of Solid State Electrochemistry, 2025)
Keywords: Capacitance; Chemical engineering; Chemistry; Electrochemistry; Electrode; Energy storage; Graphene; Inorganic chemistry; Materials science; Metallurgy; Nanotechnology; Oxide; Physical chemistry; Supercapacitor; Synthesis; Ternary operation; Thermodynamics; X-ray diffraction; dept.phy

Effect of multi-wall carbon nanotubes on electrochemical performances of MnO2 - Singhal, Rahul; Saini, Bhagirath; Kiehnle-Benitez, Monica; Sadowski, Thomas; Broadbridge, Christine; Scanley, Jules; LeMaire, Peter K.; Sharma, Rakesh K. (AIP Advances, 2022)
Composites of MnO2/multi-wall carbon nanotubes (MWCNTs) were prepared using different weight ratios of MWCNTs: KMnO4 (1:2, 1:5, 1:10, 1:15, 1:20, and 1:25) using a one-pot hydrothermal method. The synthesized materials were physically characterized by x-ray diffraction, transmission electron microscopy (TEM), field emission-scanning electron microscopy (FE-SEM), (Brunauer–Emmett–Teller) BET, and thermogravimetric analysis. TEM and SEM studies indicate that MnO2 is homogeneously entangled with MWCNTs. The electrochemical performance evaluation was performed in a 3-electrode system using MnO2/MWCNT electrodes coated onto a Ni mesh as the working electrode, a Pt foil as the counter electrode, and Ag/AgCl as the reference electrode. The specific capacitance was obtained from charge–discharge studies at varying current densities between 0.5 and 5 A/g. The specific capacitance of MWCNT-KMnO4 (1:10, 1:15, and 1:25) samples was obtained as 114, 164, and 100 F/g, respectively, at a current density of 1 A/g.
Keywords: dept.phy; peer-reviewed

Synthesis and characterization of CuS, CuS/graphene oxide nanocomposite for supercapacitor applications - Singhal, Rahul; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Sharma, Rakesh K. (AIP Advances, 2020)
Supercapacitors or electrochemical capacitors are receiving greater interest because of their high-power density, long life, and low maintenance. We have synthesized CuS nanoparticles and graphene oxide (CuS-GO) nanocomposites for supercapacitor applications because of their low cost and excellent electrochemical properties. The phase purity of each material was determined using powder XRD studies. The bandgap was determined by UV-visible spectrophotometric studies. Scanning electron microscope and transmission electron microscope images revealed the nano-scale morphology of the synthesized particles. All the electrochemical measurements were conducted in a standard three-electrode configuration, using a platinum wire as the counter electrode and Hg/HgO as the reference electrode. CuS and its composites with graphene oxide on nickel foam were used as working electrodes. All the electrochemical measurements were performed in 3M KOH solution. The CuS-GO nanocomposite electrode showed a specific capacitance of 250 F/g, 225 F/g, 182 F/g, 166 F/g, 161 F/g, and 158 F/g at a current density of 0.5 A/g, 1 A/g, 5 A/g, 10 A/g, 15 A/g, and 20 A/g, respectively. CuS-GO electrodes showed a specific capacitance retention of 70% after 5000 charge-discharge cycles at a current density of 5 A/g. © 2020 Author(s).
Keywords: Capacitance; Charge-discharge cycle; Copper compounds; Electric discharges; Electrochemical capacitor; Electrochemical electrodes; Electrochemical measurements; Foams; Graphene; Mercury compounds; Nanocomposite electrodes; Nanocomposites; Potassium hydroxide; Scanning electron microscopy; Spectrophotometric study; Supercapacitor; Supercapacitor application; Synthesis (chemical); Synthesis and characterizations; Transmission electron; Transmission electron microscopy; dept.phy; peer-reviewed

Effect of reduce graphene oxide (Rgo) on electrochemical performance of Cus for supercapacitor applications - Singhal, Rahul; Thorne, David; Chaudhary, Manika; Bhardwaj, Shiva; Abazi, Rilind; Gupta, Ram K.; Scanley, Jules; Broadbridge, Christine C.; Singh, B. P.; LeMaire, Peter K.; Sharma, Rakesh K. (2023)
CuS and CuS-rGO nanocomposites were synthesized by the hydrothermal method. The synthesized CuS and rGO-CuS nanocomposite materials were physically characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) and were evaluated electrochemically for supercapacitor applications. The specific capacitance of CuS was determined to be 207 F/g, 150 F/g, and 97 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively. The rGO-CuS nanocomposite showed improved specific capacitance of 350 F/g, 251 F/g, and 149 F/g at a current density of 0.5 A/g, 5 A/g, and 20 A/g, respectively.
Keywords: CuS; SEM; Supercapacitors; dept.phy; rGO; specific capacitance

Study of MnO2-Graphene Oxide nanocomposites for supercapacitor applications - Singhal, Rahul; Fagnoni, Justin; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Manivannan, Mani; Pandey, Rishikesh (MRS Advances, 2019)
Graphene oxide (GO)/MnO2 nanocomposites were synthesized by adding KMnO4 in a solution of water and ethanol (3:1), containing 10 mg of GO. Brown precipitates were obtained after a continuous stirring for 1 hr. The precipitates were then washed with deionized water (DI) water and dried to obtain the MnO2-GO nanocomposites. Pure MnO2 was also synthesized using the same method without GO for the comparison. X-ray diffraction pattern confirm δ-MnO2 type of MnO2 with birnessite type MnO2 structure. The TEM images show the average diameter of MnO2 nanorods as 15 nm. Electrochemical characterizations were carried out in an aqueous solution of 3M KOH. Charge-discharge studies were carried out between 1A/g to 20 A/g current range. The MnO2-GO nanocomposites showed improved electrochemical performances. The capacitance of MnO2 and MnO2-GO electrodes was found to be as 300 F/g, and 350 F/g, respectively at a current of 0.5 A/g. © 2019 Materials Research Society.
Keywords: Average diameter; Charge-discharge; Continuous stirrings; Current range; Deionized water; Electric discharges; Electrochemical characterizations; Electrochemical performance; Energy storage; Graphene; Graphene oxide nanocomposites; Manganese oxide; Nanocomposites; Nanorods; Potassium hydroxide; Raman spectroscopy; Supercapacitor; Supercapacitor application; X ray diffraction; dept.phy; energy storage; graphene; peer-reviewed; x-ray diffraction (XRD)